An Efficient Iron(III)‐Catalyzed Aerobic Oxidation of Aldehydes in Water for the Green Preparation of Carboxylic Acids. (2nd March 2017) - Yu, Han; Ru, Shi; Dai, Guoyong; Zhai, Yongyan; Lin, Hualin; Han, Sheng; Wei, Yongge
Abstract: The first example of a heterogeneous iron(III)‐catalyzed aerobic oxidation of aldehydes in water was developed. This method utilizes 1 atmosphere of oxygen as the sole oxidant, proceeds under extremely mild aqueous conditions, and covers a wide range of various functionalized aldehydes. Chromatography is generally not necessary for product purification. Its operational simplicity, gram‐scale oxidation, and the ability to successively reuse the catalyst, make this new methodology environmentally benign and cost effective. The generality of this methodology gives it the potential to be used on an industrial scale.